Truthfulness and the permissibility of Falsehood in the Jewish tradition. Issue 2 (4th May 2017) - Homolka, Walter
Abstract: In this article, I deal with the concept of truth and lie in Jewish traditional literature, examining its development in the Hebrew Bible and rabbinic literature. An essential aspect in understanding this concept is the dualism of 'good' and 'evil' impulses and the free will of human beings, who were created in the image of God and have the choice to decide between right and wrong.